Etlingera elatior-mediated synthesis of gold nanoparticles and their application as electrochemical current enhancer - Azri, Farah Asilah; Selamat, Jinap; Sukor, Rashidah; Yusof, Nor Azah; Ahmad Raston, Nurul Hanun; Nordin, Noordiana; Jambari, Nuzul Noorahya (MDPI, 2019)
This work presents a simple green synthesis of gold nanoparticles (AuNPs) by using an aqueous extract of Etlingera elatior (torch ginger). The metabolites present in E. elatior, including sugars, proteins, polyphenols, and flavonoids, were known to play important roles in reducing metal ions and supporting the subsequent stability of nanoparticles. The present work aimed to investigate the ability of the E. elatior extract to synthesise AuNPs via the reduction of gold (III) chloride hydrate and characterise the properties of the nanoparticles produced. The antioxidant properties of the E. elatior extract were evaluated by analysing the total phenolic and total flavonoid contents. To ascertain the formation of AuNPs, the synthesised particles were characterised using the ultraviolet-visible (UV-Vis) spectroscopy, Fourier transform infrared (FTIR) spectroscopy, high-resolution transmission electron microscopy (HRTEM), energy-dispersive X-ray (EDX) microscopy, and dynamic light scattering (DLS) measurement. The properties of the green synthesised AuNPs were shown to be comparable to the AuNPs produced using a conventional reducing agent, sodium citrate. The UV-Vis measured the surface plasmon resonance of the AuNPs, and a band centered at 529 nm was obtained. The FTIR results proved that the extract contained the O-H functional group that is responsible for capping the nanoparticles. The HRTEM images showed that the green synthesized AuNPs were of various shapes and the average of the nanoparticles’ hydrodynamic diameter was 31.5 ± 0.5 nm. Meanwhile, the zeta potential of −32.0 ± 0.4 mV indicates the high stability and negative charge of the AuNPs. We further successfully demonstrated that using the green synthesised AuNPs as the nanocomposite to modify the working surface of screen-printed carbon electrode (SPCE/Cs/AuNPs) enhanced the rate of electron transfer and provided a sensitive platform for the detection of Cu(II) ions.